Labour Productivity in Mixed-model Manual Assembly Changeovers - Miqueo, Adrian; Torralba, Marta; Yagüe, José Antonio (Jornada de Jóvenes Investigadores del I3A, 2020)
In a demand context of mass customisation, Industry 4.0 technologies open new possibilities of increased productivity and flexibility for mixed-model assembly lines. Analytical and parametric analysis is used to better understand the productivity losses of model changeovers as a preliminary step to develop an Assembly 4.0 implementation methodology.